La prise en compte de l’expérience dans un dispositif de formation : Tensions et stratégies organisationnelles - Marie-Christine Presse (Questions Vives, 2013)
Experience recognition and its different forms around the world open particularly in France, a new access pathway to a certification. The various research on the APL (Accreditation of Prior Learning) or in French,VAE (Validation des Acquis de l’Expérience) since 2002 (Press, 2008) have helped to set up a training program at the university. Issues and effects of this device are the objects of the analysis. The matter is not therefore to provide some answers on access opportunities to the experience, but to understand the tensions that its use creates. It appears that the greatest tensions have to be seen in relation to the training space.